The Effect of Product Quality, Price and Quality of Service on Consumer Satisfaction (Case study in Perumahan Sawangan Indah Depok) - Haryantini Haryantini (Jurnal Pemasaran Kompetitif, 2023)
This study aims to determine the effect of product quality, price and service quality on MyRepublic consumer satisfaction in Serua Permai Housing, South Tangerang. This research method is quantitative method. The population in this study were 243 users with a sample of 151 respondents. The analytical model used is Multiple Linear Regression which is processed using the SPSS version 26 application program, data is collected using questionnaires. Based on the results of this research, it shows that product quality  has a significant effect on consumer satisfaction. Price has a significant effect on Consumer Satisfaction. Service Quality has a significant effect on consumer satisfaction and and simultaneously Product Quality, Price and Service Quality has significant effect on MyRepublic Consumer Satisfaction in Serua Permai, South Tangerang.